2001
DOI: 10.2486/indhealth.39.189
|View full text |Cite
|
Sign up to set email alerts
|

A Patient with Asbestos-Induced Lung Cancer Complicated by Silicosis.

Abstract: A 76-year-old male died of lung cancer. At first, he was diagnosed as a silicosis, because he had worked for 30 years as a caster in shipyard and large opacities detected by chest x-ray and CT scanning. After the operation of lung cancer, numerous asbestos bodies were observed in the operated lung tissues. The detailed occupational inquiry revealed his asbestos use as a caster in shipyard. Early stage of asbestosis was suspected by chest CT scanning, but not definitely diagnosed in premortal examinations. Asbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Moreover, silicosis is found to be not only a respiratory disease, but also can be associated with other disorders. It has been reported that silicosis was associated with lupus-like autoimmune disease [11] and silicosis could complicate existing diseases such as lung cancer [12]. Others found pericardial plague as a complication of silicosis in one patient [13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, silicosis is found to be not only a respiratory disease, but also can be associated with other disorders. It has been reported that silicosis was associated with lupus-like autoimmune disease [11] and silicosis could complicate existing diseases such as lung cancer [12]. Others found pericardial plague as a complication of silicosis in one patient [13].…”
Section: Introductionmentioning
confidence: 99%